Thermal adaptation response of Glaciozyma antarctica PI12: statistical analysis of gene expression under temperature conditions - Nurul Sarah Izzati Zahid; Nora Muda (Penerbit Universiti Kebangsaan Malaysia, 2025)
Glaciozyma antarctica PI12, a psychrophilic yeast isolated from Antarctic Sea ice, exhibits remarkable cold adaptation mechanisms. While its optimal growth occurs at 12 °C, its transcriptional response across broader temperature ranges remains poorly understood. We analysed the expression patterns of 7,853 genes under varying temperatures (-12 °C to 20 °C) and exposure times (6 and 24 h) to understand thermal stress responses. Our findings showed that G. antarctica exhibits maximum transcriptional changes (182.4% increase in differentially expressed genes) at 12 °C after 24 h exposure compared to -12 °C/6 h, suggesting an optimal temperature range for cellular adaptation. Gene expression decreased at higher temperatures (16 °C & 20 °C), indicating potential thermal stress responses. Temporal analysis showed that 24-h exposure elicited stronger transcriptional responses compared to 6-h exposure, highlighting the time-dependent nature of thermal adaptation. Statistical modelling using negative binomial regression supported these biological observations. Our findings provide new insights into G. antarctica’s transcriptional response to thermal stress and establish a framework for analysing complex gene expression patterns in psychrophilic organisms.